Beef cows gtrointestinal nematode infection in the brazilia - Catto, João Batista (Pesquisa Agropecuaria Brasileira, 2014)
Intensity and seasonality of nematodo infection was observed on dry and lactating cows during three years through faecal analyses and necropsies. The infection rato on necropsiod animaIs, although 10w the whole year wero more intensivo during tho dry soason. It is concludod that in the Pantanal region the strategic uso of antholmintics on adult cows is not necessary.